2019
DOI: 10.1111/pere.12301
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal and bidirectional association between parenting stress and couples' relationship quality

Abstract: This study examined the longitudinal and bidirectional association between parenting stress and relationship quality, and whether the associations differed between married and cohabiting couples, using cross‐lagged panel models (CLPM) and random‐intercept cross‐lagged panel models (RI‐CLPM). Using data from the Fragile Families and Child Well‐being Study, the findings indicated that the RI‐CLPM model provided a better fit to the data compared to the CLPM model for mothers and fathers. The RI‐CLPM results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Lastly, previous research has shown that by increasing parental mindfulness, one can improve child behavioral health outcomes (Bögels et al, 2014; Coatsworth et al, 2018). Given that children's behavioral difficulties can contribute to parenting stress (Williams & Parra, 2019) and to coparents’ relationship satisfaction (Mark & Pike, 2017), the clinical significance of the current findings is two‐fold.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Lastly, previous research has shown that by increasing parental mindfulness, one can improve child behavioral health outcomes (Bögels et al, 2014; Coatsworth et al, 2018). Given that children's behavioral difficulties can contribute to parenting stress (Williams & Parra, 2019) and to coparents’ relationship satisfaction (Mark & Pike, 2017), the clinical significance of the current findings is two‐fold.…”
Section: Discussionmentioning
confidence: 93%
“…Although fewer examinations of mindful coparenting exist, the broader literature on mindfulness may assist in conceptualizing how mindful coparenting can improve relationship quality. For example, mindfulness has been highlighted as a helpful tool in reducing parenting stress, which has been shown to increase relationship satisfaction among couples (Williams & Parra, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experiences with a high number of participating families with a high level of marital discord, Bandoroff and Scherer [29] further argued that dysfunctional families are less suited for intensive wilderness treatment due to the lack of capacity for cohesive family processes. Previous findings have indicated that parenting stress and couples' relationship quality are empirically related [48]. Furthermore, participant characteristics presented in the study of juvenile status offenders by Pommier and Witt [2], also indicate a relationship between parental marital status and child difficulties.…”
Section: Evidence For Practicementioning
confidence: 95%
“…Interestingly, prior research has shown that the association between stress and relationship functioning may be somewhat more complex when examined within individuals (Hilpert et al, 2018; Milek et al, 2015; Williams & Parra, 2019). While some studies found that stress may (directly or indirectly) negatively impact relationship functioning on an intrapersonal level (Lavee & Ben-Ari, 2007; Sears et al, 2016), being more stressed than usual is not consistently associated with reduced relational well-being.…”
Section: Stress In Times Of the Covid-19 Pandemicmentioning
confidence: 99%